2011
DOI: 10.1155/2011/832165
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Single Nucleotide Polymorphisms in the Adiponectin Gene with Adiponectin Levels and Cardio-Metabolic Risk Factors in Patients with Cancer

Abstract: Abstract. Objectives:The aims of this study are to (1) study the influence of polymorphisms in adiponectin gene on adiponectin levels and potential associations with breast, prostate and colon cancer; (2) investigate the associations of adiponectin levels with other adipokines and breast, prostate and colon cancers. Subjects: We measured fasting adiponectin, leptin, insulin, Sex steroids in 132 (66 females, 66 males) cancer patients and 68 age and sex matched apparently healthy subjects. Body Mass Index (BMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Adiponectin 45T/G and 276T/G gene polymorphisms are of gene polymorphisms associated with breast cancer (8,27,28). In a study by Al Khaldi et al (27), the adiponectin gene 45T>G was found more frequently in patients with breast cancer in Kuwait, and the adiponectin gene was considered to predispose for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin 45T/G and 276T/G gene polymorphisms are of gene polymorphisms associated with breast cancer (8,27,28). In a study by Al Khaldi et al (27), the adiponectin gene 45T>G was found more frequently in patients with breast cancer in Kuwait, and the adiponectin gene was considered to predispose for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Al Khaldi et al (27), the adiponectin gene 45T>G was found more frequently in patients with breast cancer in Kuwait, and the adiponectin gene was considered to predispose for breast cancer. Adiponectin 45T/G and 276 T/G polymorphisms were demonstrated to be associated with breast cancer in a study conducted in India.…”
Section: Discussionmentioning
confidence: 99%
“…A functional adiponectin (ADIPOQ) SNP, rs1501299, is significantly linked to high serum adiponectin levels [79] and BC [80], and rs1501299 (1276C.A) and rs2241766 (145T.G) are associated with this tumor in whites and African Americans [81] and populations from Kuwait [81] and South India [82]. However, ADIPOQ SNP rs1063539 is correlated with improved DFS in women with stage I-II BC [81]; however, a further polymorphism in the ADIPOR1 SNP rs7539542 is apparently associated with BC risk [83].…”
Section: Adiponectin (Adipoq) and Adiponectin Receptor-1 (Adipor1) Snpsmentioning
confidence: 99%
“…BC development in obese women is also related to a genetic susceptibility, that is specific to each ethnicity, as revealed by the analysis of several gene SNPs (Table 1). In whites, major polymorphisms associated with the BC risk in obese women include LEP-2548 AA [66], PON1 Leu55Met [68],TNF-a-308G.A [73], FTO-MC4R (FTO rs1121980; FTO rs9939609; MC4R rs17782313) [77], ADIPOQ (rs1501299 T; rs2241766 C; rs1063539 A/C) [71,80,81], IGF-I (CA)19 allele [87], and PR (rs10895068 A) [94]. In contrast, other polymorphisms of obesityrelated genes exert a protective effect (e.g., LEPR*6920A, associated with a decreased risk of BC in women with BBD [67]; LEP-2548G/G, related to the expression of low leptin mRNA levels [70]; and LEPR SNP rs11585329 [622G.T]) and have been associated with improved DFS in women with early-stage BC [71].…”
Section: Obese Women At Risk Of Bcmentioning
confidence: 99%
“…Los condrocitos regulan su concentración intracelular de glucosa mediante la expresión del transportador de membrana de glucosa (GLUT-1), sin embargo en los pacientes con gonartrosis son incapaces de regular la expresión de GLUT-1, secuestrando altas concentraciones de glucosa y produciendo especies reactivas de oxígeno y citocinas proinflamatorias como MMP 1 y 13 que inducen el inicio de un programa catalítico con destrucción de matriz y muerte celular. También se ha observado que enfermedades con respuestas inflamatorias activas como la hepatitis C, HIV y artritis reuma-toide, cursan con un estado de resistencia a la insulina 6,9,11,23,24. El funcionamiento del factor de necrosis tumoral alfa (TNF α) se encuentra alterado en los pacien-tes obesos, en pacientes con artritis reumatoide se ha observado que al administrar anticuerpos antiTNF α mejora la resistencia a la insulina, en pacientes obesos con DM2 la administración etanercep, un antagonista TNF α reduce los niveles sanguíneos de glucosa y aumenta los niveles de adiponectina.…”
unclassified